2021
DOI: 10.1111/odi.13937
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of different triggering pathways for the pathobiology of pemphigus vulgaris—A review

Abstract: Pemphigus vulgaris is an autoimmune blistering disease with an increased potential for mortality. The epithelium is key in understanding the pathobiology as it is specialized to perform functions like mechanical protection, immunological defense, and proprioception. In order to perform these array of functions, epithelial integrity is important. This integrity is maintained by a host of molecules which orchestrate the ability of the keratinocytes to function as a single unit. Desmoglein 3 antibodies formed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…The chronic increase in certain ECM components, such as hyaluronan (HA), has been associated with a shift from benign inflammation to chronic pro-inflammatory effects, contributing to OA development. [ 16 17 18 ] Therefore, the elevated levels of Complement C3 observed in our study may indicate damaged cartilage in OA patients.…”
Section: Discussionmentioning
confidence: 72%
“…The chronic increase in certain ECM components, such as hyaluronan (HA), has been associated with a shift from benign inflammation to chronic pro-inflammatory effects, contributing to OA development. [ 16 17 18 ] Therefore, the elevated levels of Complement C3 observed in our study may indicate damaged cartilage in OA patients.…”
Section: Discussionmentioning
confidence: 72%
“…Our team has extensive knowledge and research experience that has translate into high quality publications Jayasree et al [21],Sivakumar et al [22] ,Uma Maheswari et al [23],Avinash et al [24],Chaitanya et al [25], Gudipaneni et al [26], Chaturvedula et al [27], Patil et al [28] ,Ezhilarasan et al [29], Sharma et al [30], Perumalsamy et al [31], Rajeshkumar et al [32], Mehta et al [33], Rajakumari et al [34], PradeepKumar et al [35], R et al [36], Ezhilarasan et al [37] Sarode et al [38] Kavarthapu and Gurumoorthy [39] Preethi et al [40].…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained in the present study elaborate on the pathogenic role of non-Dsg AuAbs in PV. A recently published critical appraisal of different known triggering pathways in PV pathophysiology ( 38 ) emphasized that the pathogenesis of this serious disease is complex and requires an in-depth understanding of the various predisposing and provoking factors and effector mechanisms to improve the efficacy and safety of current treatments. Numerous studies conducted worldwide over the last 3 decades on anti-Dsg AuAbs convincingly demonstrated that these AuAbs can serve a reliable diagnostic marker of PV.…”
Section: Discussionmentioning
confidence: 99%